DC-DC Converter for Fuel Cell Application - Chua, Kean Yin (Universiti Malaysia Perlis, 2010)
Engineering Invention & Innovation Exhibition (ENVEX) 2010 organized by Student Affairs & Alumni Department (HEPA), Universiti Malaysia Perlis (UniMAP) with collaboration Ministry of Higher Education Malaysia (MOHE) and Ministry of Science & Technology Innovation (MOSTI) , 2nd - 4th April 2010 at Khoon Aik Hall, Kangar, Perlis.